2012
DOI: 10.1371/journal.pone.0030695
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of CCR4+ CTLA-4hi FOXP3+CD25hi Regulatory T Cells in Colon Adenocarcinomas Correlate to Reduced Activation of Conventional T Cells

Abstract: BackgroundColorectal cancer usually gives rise to a specific anti-tumor immune response, but for unknown reasons the resulting immunity is not able to clear the tumor. Recruitment of activated effector lymphocytes to the tumor is important for efficient anti-tumor responses, while the presence of regulatory T cells (Treg) down-modulate tumor-specific immunity. We therefore aimed to determine homing mechanisms and activation stage of Treg and effector T cell infiltrating colon tumors compared to cells from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 47 publications
7
52
2
Order By: Relevance
“…Instead, a significantly higher proportion of CXCR3+ cells within the EM CD4+ T cell subset was found in the majority of patients with LN involvement and a CXCR3+ TFH subset significantly increased in circulation when adenopathies were present. If looking from the Th cytokine profile point of view, our results are in contradiction to data available in the literature suggesting a gradual change in composition of the T cell microenvironment from a Th1 to a Th2 phenotype with the evolution of the disease, in order to secure the selective advantage for tumor growth [27,28]. Based on intracellular cytokines presence, a very recent study found a link between high proportions of circulating Th2 cells in B-CLL patients and the expression of the poor prognostic factor ZAP-70 [29].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Instead, a significantly higher proportion of CXCR3+ cells within the EM CD4+ T cell subset was found in the majority of patients with LN involvement and a CXCR3+ TFH subset significantly increased in circulation when adenopathies were present. If looking from the Th cytokine profile point of view, our results are in contradiction to data available in the literature suggesting a gradual change in composition of the T cell microenvironment from a Th1 to a Th2 phenotype with the evolution of the disease, in order to secure the selective advantage for tumor growth [27,28]. Based on intracellular cytokines presence, a very recent study found a link between high proportions of circulating Th2 cells in B-CLL patients and the expression of the poor prognostic factor ZAP-70 [29].…”
Section: Discussioncontrasting
confidence: 99%
“…The expression of CXCR3 on the malignant clone was previously reported to be of prognostic value for B-CLL patients [28]. In our study CXCR3 proportion within the B-CLL pool was found to be lower (not significantly, though) in the occurrence of LN/ organ involvement.…”
Section: Discussionsupporting
confidence: 51%
“…3). This was in contrast to the CD8 + non-MAIT cells, where there was a significant reduction of activated CD69 + cells in the tumor (p , 0.05), as we have previously reported (24). We also analyzed MAIT cell expression of programmed cell death protein 1 (PD-1; CD279), which has been implicated as an attenuating receptor on exhausted T cells, and also on Mycobacterium tuberculosis-reactive MAIT cells (25,26).…”
Section: Phenotype Of Colon Mait Cellsmentioning
confidence: 86%
“…This leads us to believe that redirecting Treg may be of particular importance to the treatment of micrometastases, whereas larger tumors with greater CCL22 expression may require more drastic treatment. Redirecting Treg might also be useful in other cancers where CCR4 + Treg reportedly interfere with anti-tumor responses, including colon carcinoma, lymphoma and glioblastoma (33, 34, 35). Support for our strategy is most convincing when investigating larger sample numbers, yet our materials were limited.…”
Section: Discussionmentioning
confidence: 99%